2019
DOI: 10.1007/s11829-019-09717-9
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Aceria tosichella population responses to wheat resistance genes and wheat virus transmission

Abstract: Severe winter wheat yield losses due to infestations of wheat curl mite, Aceria tosichella Keifer, and mite-transmitted viruses occur in wheat production areas of the United States and Canada. Mite infestation alone causes stunted, chlorotic plants in susceptible wheat varieties, and mites transmit Wheat Streak Mosaic (WSMV), High Plains Wheat Mosaic (HPWMoV), and Triticum Mosaic Virus (TriMV). Wheat curl mites were collected from 25 sites in Kansas, Missouri, Nebraska, Texas, North Dakota, and South Dakota in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…Many other insect pests are of importance in wheat production. The resistance gene Sm1, which acts against the orange wheat blossom midge (Sitodiplosis mosellana) has been deployed in Canada and Europe and four resistance genes (Cmc1-4) have been identified against the aforementioned wheat curl mite (A. tosichella) [183]. Other pests that are of concern to wheat production include the Sunn pest (Eurygaster integriceps), wheat stem sawfly (Cephus cinctus) (WSS) and the yellow wheat blossom midge (Contarinia tritici).…”
Section: Advances In Molecular Breeding For Insect Resistancementioning
confidence: 99%
“…Many other insect pests are of importance in wheat production. The resistance gene Sm1, which acts against the orange wheat blossom midge (Sitodiplosis mosellana) has been deployed in Canada and Europe and four resistance genes (Cmc1-4) have been identified against the aforementioned wheat curl mite (A. tosichella) [183]. Other pests that are of concern to wheat production include the Sunn pest (Eurygaster integriceps), wheat stem sawfly (Cephus cinctus) (WSS) and the yellow wheat blossom midge (Contarinia tritici).…”
Section: Advances In Molecular Breeding For Insect Resistancementioning
confidence: 99%
“…Each head was kept separate in a plastic bag in order to distinguish genetic differences between mites within a field and a grain head. Mites from each location were previously classified as biotype 1 avirulent to Cmc3 or biotype 2 virulent to Cmc3 [47] using methods of Harvey et al [46].…”
Section: Sample Collectionmentioning
confidence: 99%
“…Virulence in A. tosichella to Cmc3 has remained stable for the past 20 years [34] but recent field assessments [47] determined that 24% of A. tosichella collected from multiple locations in North America are virulent to Cmc3. Therefore, there is a real need for new information about the current geographic distribution of A. tosichella biotypes or genetic lineages throughout the U. S. Great Plains and the potential changes occurring in each.…”
Section: Introductionmentioning
confidence: 99%
“…Historically, plant virologists focused on viruses that cause disease in crops, but more recently it has been shown that viruses are asymptomatically very abundant in wild plants (Roossinck 2012. Further research on the role of viruses in wild plants has revealed details of virus-arthropod-plant relationships and indicated long-standing interactions among multiple partners (Khalaf et al, 2019;Wen-Po et al, 2017). Virus ecologists look at viruses as symbionts (Roossinck, 2015).…”
Section: Introductionmentioning
confidence: 99%